Rapid Emergence and Spread of Severe Acute Respiratory Syndrome Coronavirus 2 Gamma (P.1) Variant in Haiti. (30th August 2021) - Tagliamonte, Massimiliano S; Mavian, Carla; Zainabadi, Kayvan; Cash, Melanie N; Lednicky, John A; Magalis, Brittany Rife; Riva, Alberto; Deschamps, Marie Marcelle; Liautaud, Bernard; Rouzier, Vanessa; Fitzgerald, Daniel W; Pape, Jean William; et al.
Abstract: After an initial wave of coronavirus disease 2019 (COVID-19) in Haiti in summer 2020 (primarily lineage B.1), seropositivity for anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG) was ~40%. Variant P.1 (gamma) was introduced in February 2021, with an initially limited introduction followed by exponential local dissemination within this unvaccinated population with prior exposure to earlier SARS-CoV-2 lineages.